Medium and large-sized mammals in a premontane moist forest fragment, Atenas, Costa Rica - Cambronero, Milena; Sánchez-Calderón, Ricardo; Lobo, Rodney (Revista de Biología Tropical, 2023)
Introduction: Medium and large-sized mammals are threatened globally due to habitat loss and fragmentation. In Costa Rica, forest fragments that remain outside protected areas may serve as a refuge or corridor for these animals. Mammal presence in fragmented landscapes may be influenced by resource availability, which varies greatly in seasonal regions. Objective: To determine the species richness of medium and large-sized mammals in a forest fragment, and to examine if species diversity and detectability varied between the wet and dry season. Methods: We established 26 camera trap stations throughout the Municipal Forest of Atenas (Alajuela, Costa Rica), a 26.4 ha forest fragment that provides water to about 1 800 people. From August 2021 to April 2022, one camera trap was active at each station for 12-21 days throughout each season (dry and wet), for a total of 810 camera trap days. We applied rarefaction and extrapolation curves to characterize mammal’s species diversity and compare it between seasons. Results: We detected 19 species of mammals. The most frequently detected species were the White-nosed Coati (Nasua narica; 0.254 detections/camera trap day), and the Central American Agouti (Dasyprocta punctata; 0.163 detections/camera trap day). We also registered four species considered as endangered in Costa Rica, three felines: Puma concolor, Herpailurus yagouaroundi, Leopardus pardalis, and the Neotropical River Otter, Lontra longicaudis. Seasonality did not affect species diversity, but it influenced dominant species and detectability, which was greater during the wet season. Conclusions: Our study demonstrates how protecting small forest fragments, can help conserve endangered medium and large-sized mammals in human-dominated landscapes. Objective: We aimed to determine the species richness of medium and large-sized mammals in a forest fragment protected for water production, and to examine if species diversity and detectability varied between the wet and dry season. Methods: We established 26 camera trap stations throughout the Municipal Forest of Atenas (MFA), a 26-ha forest fragment that provides drinking water to about 1 800 people. From August 2021 to April 2022, one camera trap was active at each station for 12-21 days throughout each season (dry and wet), for a total of 810 camera trap days. We applied rarefaction and extrapolation curves to characterize mammal’s species diversity and compare it between seasons. Results: We detected 19 species of medium and large-sized mammals. The species with the highest frequency of detections were the White-nosed Coati (Nasua narica; 0.504 detections/camera trap day), and the Central American Agouti (Dasyprocta punctata; 0.377 detections/camera trap day). We also detected four species considered as endangered in Costa Rica, three felines: Puma concolor, Herpailurus yagouaroundi, Leopardus pardalis, and the Neotropical River Otter, Lontra longicaudis. Seasonality did not affect species diversity but influenced the detectability of dominant species. Discussion: The relatively high richness of mammals observed in the MFA is likely related to the surrounding land use, which is dominated by agroforestry systems (e. g., coffee plantations) and forest patches, that may contribute to animal mobility and serve as refuge in fragmented landscapes. Conclusions: Our study demonstrates how protecting ecosystem services, such as water, may also help conserving endangered medium and large-sized mammals in fragmented landscapes.